2004
DOI: 10.7227/rie.72.6
|View full text |Cite
|
Sign up to set email alerts
|

ITE Students' Attitudes to Inclusion

Abstract: This, in the wider context of schools, 'pampered mainstream providers' (Thomas and Loxley, 2001) by offering an alternative that allowed society to exclude particular children under the guise of offering something better that was separate. Increasingly, disabled people have challenged the assertion that segregated provision has any part to play in any vision of inclusion (Oliver, 1998; Tomlinson, 2000), indicating a difference in ideology from that of the UK government (DfE, 1997; FEFC, 1997). These differing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 8 publications
1
12
0
2
Order By: Relevance
“…These experiences might reduce teachers' concerns and improve their attitudes towards inclusion, as indicated by previous research (e.g. Richards and Clough 2004;Winter 2006). These kinds of experiences might also increase participants' knowledge and skills, since they provide the learning opportunities that are necessary for teachers to integrate new knowledge into practice (Brunero, Lamont, and Coates 2010).…”
Section: Educational Research 319mentioning
confidence: 77%
“…These experiences might reduce teachers' concerns and improve their attitudes towards inclusion, as indicated by previous research (e.g. Richards and Clough 2004;Winter 2006). These kinds of experiences might also increase participants' knowledge and skills, since they provide the learning opportunities that are necessary for teachers to integrate new knowledge into practice (Brunero, Lamont, and Coates 2010).…”
Section: Educational Research 319mentioning
confidence: 77%
“…The study highlights the benefits of regular and special education teacher training in the area of special education which is very useful to teacher preparation programs and school administrators preparing teacher professional development sessions. Richards and Clough (2004) examined the effects of a postgraduate program on student teachers' attitudes toward inclusion. Participants included 120 students in a oneyear, full-time Post Graduate Certificate of Education (PGCE) cohort at a United Kingdom university.…”
Section: Factors And/or Characteristics That Influence Attitudes Towamentioning
confidence: 99%
“…In addition, Avramidis et al (2000) surveyed prospective teachers' beliefs about inclusion and found a general lack of confidence in their ability to meet the requirements of Individualized Education Plans (IEPs). Furthermore, Richards and Clough (2004) found that pre-service teachers believed that inclusion would not influence or affect them personally. Research on prospective teachers has found that novice educators believe inclusion to be a positive practice, yet they do not believe they are capable of implementing inclusive practices in their classrooms, nor do they believe they will be asked to do so.…”
Section: Preparing Teachers To Work In Inclusive Settingsmentioning
confidence: 99%